أثر التكيف المهني للموارد البشرية على الأداء المتكيف: دراسة تطبيقية على العاملين بهيئة ميناء دمياط - السلنتي، لمياء السعيد Alsalanti, Lamia Alsaid (جامعة الزقازيق - كلية التجارة, 2017)
The study aimed to determine whether there were significant differences between the views of workers in Damietta Port Authority into practice concerning the degree of availability of each of the professional dimensions of Career Adaptability, and the dimensions of adaptive performance. Also, determine the impact of Career Adaptability on adaptive performance, and finally the impact of the demographic characteristics of a variable modified on the relationship between the Career Adaptability and adaptive performance, and so the application on a single sample of 326 workers Damietta Port Authority. The study found that there are differences found between the views of workers Authority Damietta Port into practice concerning the degree of availability of each of the professional dimensions of Career Adaptability, and the dimensions of adaptive performance. Also, the study found that there is a significant effect of the dimensions of Career Adaptability on adaptive performance, and the significant effect for each of the educational level, age, experience modified variables on the relationship between the Career Adaptability and adaptive performance while there was no significant effect of the type of a variable rate on this relationship.
استهدفت الدراسة تحديد ما إذا كانت هناك اختلافات معنوية بين آراء العاملين في هيئة ميناء دمياط موضع التطبيق فيما يتعلق بدرجة توافر كل من أبعاد التكيف المهني، وأبعاد الأداء المتكيف. وأيضا، تحديد اثر التكيف المهني على الأداء المتكيف، وأخيراً أثر الخصائص الديموجرافية كمتغير معدل على العلاقة بين التكيف المهني والأداء المتكيف، وذلك بالتطبيق على عينة حجمها 326 مفردة من العاملين بهيئة ميناء دمياط. وقد توصلت الدراسة إلي أنه توجد اختلافات معنوية بين آراء العاملين بهيئة ميناء دمياط موضع التطبيق فيما يتعلق بدرجة توافر كل من أبعاد التكيف المهني ، وأبعاد الأداء المتكيف أيضاً، توصلت الدراسة إلي أنه يوجد تأثير معنوي لأبعاد التكيف المهني علي الأداء المتكيف، كما يوجد تأثير معنوي لكل من المستوي التعليمي ، العمر، الخبرة كمتغيرات معدلة علي العلاقة بين التكيف المهني والأداء المتكيف بينما لا يوجد تأثير معنوي للنوع كمتغير معدل علي هذه العلاقة.
Keywords: التكيف المهنى -- الموارد البشرية -- الأداء المتكيف -- الابتكارات التكنولوجية